The professional identity of young university lecturers. - Ángela Martín-Gutiérrez; Jesús Conde-Jiménez; Cristina Mayor-Ruiz (Universitat Politècnica de València, 2014)
This article presents the experience of a teaching team, which is located in the Faculty of Education at the University of Seville. This team consists of three novice teachers and a teacher mentor, as part of the Training Program for Novice Teachers at this university. The European Higher Education Area (EHEA) noted the need to invest time and effort in the design and implementation of training programs aimed at initial teacher training college, because in the first years of experience in teaching practices is where they began to develop their own teaching identity. The general aim of this study is to detect which aspects made the construction of the professional identity of teachers who participated in the Program. The methodology used is clinical supervision cycles. The results allow us to identify four dimensions (emotional, social, educational-pedagogical, and institutional-administrative) that make up the construction of the professional identity of novice teachers. The emotional dimension becomes transversal to all others, since the emotions derived from sensations and perceptions present themselves to young university lecturers before the challenges and difficulties that surround them, seem to mark deeply the teacher identity. The active methodology of clinical supervision cycles allows novice teachers to become aware of aspects and dimensions that shape their professional development. This awareness is the first step in establishing improvement proposals or strategies to help overcome difficulties encountered in the process of construction and development of university professional identity.